The self power of a clamped circular plate. An analytical estimation - Rdzanek, W. P.; Rdzanek, W. J. (Archives of Acoustics, 2003)
A low frequency approximation for the self power of a clamped crcular plate is presented in a form useful for some efficient numerical computations. The approximation is precise enough within nearly the whole low frequency range. It is assumed that the plate’s vibrations are time harmonic and axisymmetric. The approximation can be used for some further computations of the total sound power radiated by the excited plate in an acoustic fluid.